2005
DOI: 10.2106/jbjs.d.02768
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Calcar-Replacement Hemiarthroplasty Compared with Intramedullary Fixation of Unstable Intertrochanteric Fractures<sbt aid="961139">A Prospective, Randomized Study</sbt>

Abstract: Therapeutic Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 23 publications
3
67
1
3
Order By: Relevance
“…[19,20] No implant failure was reported in the studies, which evaluated cementless hemiarthroplasty for unstable intertrochanteric fractures in elderly patients. [2,4,5,10,11] Even in cementless modular hip arthroplasty after failed trochanteric fracture fixation, none of the patients required reoperation due to the loosening of femoral prosthesis. [21] Our current study also supported the results reported in the literature and no implant loosening or failure was observed during 2 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19,20] No implant failure was reported in the studies, which evaluated cementless hemiarthroplasty for unstable intertrochanteric fractures in elderly patients. [2,4,5,10,11] Even in cementless modular hip arthroplasty after failed trochanteric fracture fixation, none of the patients required reoperation due to the loosening of femoral prosthesis. [21] Our current study also supported the results reported in the literature and no implant loosening or failure was observed during 2 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[3] The treatment of unstable intertrochanteric femur fractures is very challenging and is still a matter of discussion, especially in elderly patients. [4] Studies comparing internal fixation and hemiarthroplasty for unstable intertrochanteric femur fractures in elderly patients state that hemiarthroplasty is an alternative treatment with earlier mobilization and the same functional outcome compared to internal fixation. [4,5] Although hemiarthroplasty has become popular for intertrochanteric femur fractures in elderly patients, there is no consensus whether cementless or cemented hemiarthroplasty is a better option.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So kommt es laut Literatur in 12-32 % der Fälle zum revisionspflichtigen Versagen der Osteosynthese [17, 23]. Daher ist bei pertrochantären Frakturen neben der Osteosynthese der primäre endoprothetische Ersatz eine Therapieoption, die zunehmend in den Fokus rückt und an den Operateur nicht selten große Herausforderungen stellt [65,66,67,68,69]. Parker et al [70] haben in einer Cochrane-Analyse die beiden Verfahren Osteosynthese vs. Hemiprothese in der Versorgung der extrakapsulären Frakturen des proximalen Femurs analysiert.…”
Section: Primärer Endoprothetischer Ersatz Bei Instabilen Pertrochantunclassified
“…Parker et al [70] haben in einer Cochrane-Analyse die beiden Verfahren Osteosynthese vs. Hemiprothese in der Versorgung der extrakapsulären Frakturen des proximalen Femurs analysiert. Diese Arbeit basiert auf 2 randomisierten Studien mit insgesamt 148 Patienten [68,71] und bietet keine klare Evidenzlage. Beide Studien zeigten einen erhöhten Bedarf an Bluttransfusionen bei Patienten mit primär endoprothetischem Ersatz.…”
Section: Primärer Endoprothetischer Ersatz Bei Instabilen Pertrochantunclassified